An FEM analysis of metal matrix composite machining - Pramanik, Alokesh; Zhang, Liangchi; Arsecularatne, Joseph (Japan Society for Precision Engineering, 2006)
This paper investigates the matrix deformation and tool-particle interactions during machining of a metal matrix composite (MMC) using finite element simulations. Based on the geometrical orientations, the interaction between tool and reinforcements was categorized into three cases: particles along, above and below the cutting edge. The development of stress and strain fields in the MMC was analyzed and physical phenomena such as tool wear, particle fracture, debonding, displacements and inhomogeneous deformation of matrix material were explored and compared with the experimental results in the literature.